2008
DOI: 10.3201/eid1401.071240
|View full text |Cite
|
Sign up to set email alerts
|

Population-based Survey of Invasive Bacterial Diseases, Greenland, 1995–2004

Abstract: Invasive bacterial disease occurs frequently among native populations in the Arctic. Although a variety of bacteria are involved in invasive bacterial disease in Greenland, Streptococcus pneumoniae , Escherichia coli , Staphylococcus aureus , and other staphylococci are responsible for most cases (69%); incidence varies according to region and ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Increased incidence of SAB according to ethnicity has previously been noted [7,8,16-18], however, this study is unique in the size of the disparity observed and the finding that the disparity is particularly marked for community-associated MRSA. There are key public health implications arising from these findings regarding strategies to prevent staphylococcal infections in Indigenous communities.…”
Section: Discussionmentioning
confidence: 59%
“…Increased incidence of SAB according to ethnicity has previously been noted [7,8,16-18], however, this study is unique in the size of the disparity observed and the finding that the disparity is particularly marked for community-associated MRSA. There are key public health implications arising from these findings regarding strategies to prevent staphylococcal infections in Indigenous communities.…”
Section: Discussionmentioning
confidence: 59%
“…The psychosocial stress is reflected in alcohol abuse, violence and suicide, and these have all been shown to be associated with changes in lifestyle and living conditions (Curtis et al 2005) that are affected by the impacts of changing snow conditions on traditional activities (subsistence hunting and gathering as well as recreational activities). Currently, many Arctic indigenous and other resident populations are experiencing high mortality rates from injury and suicide and higher hospitalization rates for infants with pneumonia, meningitis and respiratory infections (Heikkinen et al 2008;Meyer et al 2008). Wintertime mortality and morbidity will decrease with higher environmental temperatures (Näyhä 2005).…”
Section: Socio-economic Processes and The Role Of Snow Covermentioning
confidence: 99%
“…Recent research indicates that disinfection and removal of human pathogens in some Arctic wastewater stabilization ponds may be inadequate (Huang et al 2014). The risk of human exposure to inappropriately treated wastewater adds to the already high rates of infections, such as tuberculosis and methicillin-resistant Staphylococcus aureus (MRSA), in Alaska, Greenland, and Canadian indigenous populations (Meyer et al 2008;Vandenesch et al 2003, Byrd et al 2009, Bourgeois et al 2018. Furthermore, the continuing environmental change in the Arctic could significantly influence the fate of pathogenic microorganisms discharged from wastewater treatment systems into marine and freshwater environments, posing increased human health risks (Dudley et al 2015;Hueffer et al 2011;Parkinson et al 2014).…”
Section: Editorialmentioning
confidence: 99%